Omnibus Law dan Substansi Perubahan Undang-Undang Tentang Perpajakan - Dedi Haryadi; Hengky Leon; Ricky, Ricky (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The omnibus law on taxation in Indonesia is part of the government's efforts to reform the tax system to increase investment competitiveness and support economic growth. These reforms include a range of changes in tax regulations intended to simplify tax administration, expand the tax base, and improve tax compliance. Changes to the law occurred through Law Number 11 of 2020 and changed the content of the KUP Law, Income Tax Law and VAT Law. This change in law was then socialized to the students of Santa Maria Catholic Vocational School Pontianak City in the form of providing knowledge and answering situation analysis about challenges and implementation. It can be concluded that through this Job Creation Law, several important rules contained in the Income Tax Law, the VAT Law and the KUP Law have been changed. Changes in the law substantially renew, clarify, facilitate and provide competitive rates for the ease of doing business cluster in the field of taxation It is hoped that this presentation can support the knowledge of Santa Maria Catholic Vocational School students about the importance of the tax system which later after the students graduate and have an income, they will also become taxpayers and comply with existing taxation according to the law.